OperatÄ±on and Management of TrÄ±cycle (Keke Napep) As a Mean of PublÄ±c Transport in MÄ±nna, NÄ±gerÄ±a - Ajiboye, Araoye Olarinkoye; Ohida, Muhammed Etudaiye; Abdullahi, Muhammed Itopa; Komolafe, Bolaji Olaide (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
Tricycle (KEKE NAPEP) as a mean of public transport in Nigeria has come to stay and becoming a dominant mean for public transport in Minna, Nigeria. This paper aimed to assess the operation and management of Tricycle as a means of public transport in Minna. Two separate structured questionnaires were used to collect data on the operators and passengers perceptions on the tricycle operations. The result was subjected to a hypothetical test, using ANOVA and Chi-Square, and descriptive technique as a method of analysis. The findings reveal that a high percentage (38.2%) of KEKE NAPEP ownership is on the hire purchase agreement, and there are high maintenance expenses (67.6%). Also, possible recommendations were provided on how to curb the identified challenges, which include; ACOMORAN should mediate between her members and investors in seeking loans and conclusion of hire purchasing agreement. Furthermore, they should ensure favourable loan tenure for her members; the government should subsidise spare parts and ensure proper road maintenance so that the rates of wear and tear of vehicles part are reduced.